THE SEAMY SIDE OF AMERICAN CAPITALISM IN JOHN STEINBECK'S THE GRAPES OF WRATH - Fuad Hasyim (Universitas Gadjah Mada, 2014)
This article is an attempt to study Steinbeck’s vision of the American system of capitalism during 1930’s as causing the greatest economic crisis in American history. The study particularly observes the growth of materialistic values in this era. The main discussion concerns the dramatic journey of Joad’s family toward California as reflected in The Grapes of Wrath.With an interdisciplinary approach, the study examines the novel to comprehend the author’s view about his social phenomena. This is a kind of qualitative research in which the researcher applied library research on The Grapes of Wrath. The data gathered from bibliographical sources was analyzed and written descriptively to describe the seamy side of capitalism in America.The result of this research shows that material success is not the human’s only orientation in his life. The great depression and tragic life of Oklahoma tenant farmers were viewed by the author as due to the impact of uncontrolled American Capitalism in 1930’s. The seamy sides of American Capitalism such as greed, selfishness, corruption, and consumptive behavior, etc. have been described by the author as source of the extensive destruction among American people.